Gay By The Bay: Feeling Queer, Feeling Newfoundland - Pearce, Ky (2018)
While growing up in rural Newfoundland, I often felt that my identities as a rural Newfoundlander and a queer person were in conflict. Inspired by my own experiences and those of my loved ones, I began this research with the primary goal of documenting the experiences of rural Newfoundland’s queer youth in such a way that carefully maintained the autonomy of my participants and their voices. However, as the study progressed it became clear that my broad exploration was trying to answer one question: given the difficult – often painful and traumatic – experiences of queer youth in rural Newfoundland, could our identities as rural Newfoundlanders and queer people easily coexist? This thesis attempts to document the experiences of queer rural Newfoundlanders while asking why and if the identities of queer and rural Newfoundlander are irreconcilable. This work is based upon narratives and experiences I have collected from seven queer youth who have lived or are currently residing on Newfoundland’s rural west coast. I have coupled my participant’s narratives with my own in recognition that this research has been a profoundly personal act of introspection for me. I analyze our experiences in reference to structures of feeling, a concept coined by Marxist Raymond Williams to describe one way that culture and power interact. My findings suggest that queer youth, from diverse backgrounds and of diverse identities, have extreme difficulty reconciling their identity as a rural Newfoundlander with their queer identity. My findings also suggest that many queer youths in rural Newfoundland are as strongly affected by homonormativity and metronormativity as they are by cis-heterosexism and queerphobia. Finally, this research has shown that queer youth in rural Newfoundland, and likely elsewhere, would benefit from readily visible queerer forms of queerness. M.A.